UTERINE LEIOMYOSARCOMA IN THREE CAPTIVE WILD LIONS (PANTHERA LEO) - N, JAYASREE; SRILATHA, CH; NSAILAJA, N; VENU, R; VARAPRASAD, WLNV (The Indian Journal of Animal Reproduction, 2016)
Three lions showed the presence of creamy white pus in the uterus and thickening of uterine wall. The grayish white small to big sized hard masses present on the uterine body and horns were diagnosed as leiomyosarcoma on histopathological examination with parallel and interlaced arrangement of smooth muscle fibres and cigar shaped hyperchromatic nucleus.